PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS EDUCANDY MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IV SD NEGERI 233 PALEMBANG - Putri Permata Sari; Dessy Wardiah; Pratama, Aldora (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop Educandy-based learning media on the material of Origin Chapter 7 of grade IV elementary school that is valid and practical. This research is an R&D study using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data collection technique used is a student response questionnaire. The results of data analysis in this study indicate that the Educandy-based learning media developed with a very valid category based on the validation questionnaire from the validator consisting of 2 lecturers and 1 teacher of SD 233 Palembang which is assessed from all aspects, namely media, language and materials with a percentage obtained 97.91%. Educandy-based learning media developed with a very practical category based on student repos questionnaires obtained a percentage of 94,69% (one to one) and 94,60% (small group). And the results of the overall student questionnaire responses obtained a percentage of 92,63%. Thus it can be concluded that the development of Educandy-based media is declared valid and practical.